Penerapan Model Discovery Learning untuk Meningkatkan Hasil Belajar Mahasiswa Pada Mata Kuliah Pelayanan Prima di Jurusan PKK FT UNM - Ratnawati T; Syamsidah Syamsidah; Besse Qurani (Seminar Nasional LP2M UNM, 2022)
Abstract. This research is a classroom action research that aims to determine the application of the Discovery Learning Model to Improve Student Learning Outcomes in the Excellent Service Course in the PKK FT UNM Department. The subjects of this study were students who programmed the Excellent Service course as many as 27 people. This research was conducted in 2 (two) cycles. The data collection method used pre-test and post-test to determine student learning outcomes, observation sheets to determine the implementation of discovery learning learning models and documentation. The data were analyzed descriptively quantitatively. The results showed that student learning outcomes have increased. The average value of student learning outcomes in the first cycle the value of students' cognitive aspects is 82.5 with a percentage of 93% and in the second cycle it increases to 87.5 with a percentage of 100%. In the first cycle the affective aspect of the students was 77 with a percentage of 85% and in the second cycle it increased to 84 with a percentage of 100%. The first cycle of psychomotor aspects of students was 80 with a percentage of 89% increased to 85 with a percentage of 100% in the second cycle. Based on these results, it proves that the discovery learning model in the excellent service course can improve student learning outcomes in the PKK FT UNM major. Keywords: Discovery Learning, Learning Outcomes, Excellent Service